I Don't Like It: Pauline Pantsdown and the Politics of the Inauthentic - Stratton, Jon (John Libbey and co, 2000)
In modernity social identity has been related to authenticity, and both have been established by virtue of reductive, foundationalist claims to essence. Pauline Pantsdown, and her songs, both activate in different, but complimentary, ways what I shall call the politics of inauthenticity. As a satirical attack on the claims of Pauline Hanson, the Pantsdown persona operates as a camp interrogation of Hanson's own image, an image which gains much of its effectiveness by its claim not to be an image but, rather, to be the public face of somebody who is not a politician and who is, in fact, just an 'ordinary Australian,' to use one of Hanson's catch phrases(4). Indeed, the very name 'Pantsdown' suggests the revelation of something that Hanson is keeping hidden behind her image. I will argue that Pantsdown's political use of the camp aesthetic takes place in the social context of a carnivalesque mocking of Hanson's public image(5). Today, cultural theory tends to attack and critique essentialist notions, privileging the idea of discourse and of cultural constructivism. In discussions of sex and sexuality, queer theory, with its emphasis on performance, is replacing the more traditional assertions of gay and lesbian identity(6). However, in practice, essentialist understandings of identity are still generally assumed. In everyday life, therefore, the Pantsdown persona tends to operate as an undermining of Hanson's claim to authenticity. However, it can also be read as a radical and celebratory critique of the very notion of authenticity, as a harbinger of a new politics of play and performance which might, at least, supplement the dominant, exclusionary politics of identity. In this article I emphasise how the Pauline Pantsdown persona works within the modern binary of authentic/inauthentic because this is still the dominant paradigm in everyday life(7).